2020
DOI: 10.1021/acs.langmuir.0c01193
|View full text |Cite
|
Sign up to set email alerts
|

Negative Pressure within a Liquid–Fluid Interface Determines Its Thickness

Abstract: The density within the interface between two fluid phases at equilibrium gradually changes from that of one phase to that of the other. The main change in density, according to experimental measurements, practically occurs over a finite distance of O [1 nm]. If we assume that the average stress difference within the interface is on the order of magnitude of ambient pressure, then the Bakker equation implies that for a liquid with surface tensions, say ∼50 mN/m, we get an interface thickness of ∼500 nm. This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…In addition, in the process of negative pressure sealing drainage, negative pressure can produce pullout effect, which can stimulate the proliferation of granulation tissue, allowing the wound to heal quicker. 16 , 17 Our study showed that dressing change times, healing time and treatment cost for patients in the Group-II was significantly lower than in Group-I Additionally, in agreement with previous studies, we showed that negative pressure sealing drainage technology was associated with higher patient satisfaction. It further proves the effectiveness of negative pressure sealing drainage technology in the nursing of necrotizing fasciitis.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, in the process of negative pressure sealing drainage, negative pressure can produce pullout effect, which can stimulate the proliferation of granulation tissue, allowing the wound to heal quicker. 16 , 17 Our study showed that dressing change times, healing time and treatment cost for patients in the Group-II was significantly lower than in Group-I Additionally, in agreement with previous studies, we showed that negative pressure sealing drainage technology was associated with higher patient satisfaction. It further proves the effectiveness of negative pressure sealing drainage technology in the nursing of necrotizing fasciitis.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the value of interaction energy, Δ F , was around −3 mN m −1 for all solutions. The negative value is consistent with the typical negative pressure within the interfacial layer (Srebnik and Marmur, 2020). The results demonstrate a weak influence of glycerol on the interaction energy (Dashnau et al, 2006; Egorov et al, 2013).…”
Section: Resultssupporting
confidence: 85%
“…This explains why 2D materials are irreversibly pinned to fluid interfaces like spheroidal particles. , However, the characteristic length scales of a spheroidal and monolayer graphene particle are vastly different in the direction normal to the plane of the interface (side view). Spheroidal particles are isotropic and maintain a characteristic length scale (∼10 3 nm) that is much greater than the thickness of a fluid–fluid interface (∼10 –1 –10 0 nm), , while monolayer graphene particles have a thickness (∼10 –1 nm) that is commensurate with the length scales of out-of-plane thermal motions of a fluid–fluid interface ( i.e ., capillary waves) . This results in graphene particles being more sensitive to thermal fluctuations of a fluid–fluid interface than spheroidal particles, and small variations in the position of graphene particles normal to the interface could induce neighboring graphene particles to overlap and stack due to attractive, face-to-face van der Waals forces, as observed in MD simulations. , Yet, there is an apparent discord between simulations and experiments, as experimental evidence has demonstrated laterally aggregated and only partially overlapped monolayer particles even after compression to high particle densities. ,, …”
Section: Introductionmentioning
confidence: 99%